Development of Animaker-Based Learning Media to Improve Students' Mathematical Reasoning Ability on Comparison Materials - Sulastri, Desi; Nurhikmayati, Iik (JPMI (Jurnal Pendidikan Matematika Indonesia), 2025)
This study aims to develop Animaker-based learning media to improve students' mathematical reasoning skills on comparison materials. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research was limited to the Development stage. The research subjects were 23 8th grade students at SMP Negeri 6 Majalengka. The instruments used in this study were observation, interview, and questionnaire in the form of validation sheets and practicality sheets. The learning media developed in the form of animated videos that integrate mathematical concepts with interesting visualizations to facilitate student understanding. The results showed that Animaker-based learning media was valid with an average score of 88.5% media expert validation and 84% material expert validation. The practicality of this media is also considered very good with a teacher practicality score of 92.9% and student practicality of 90.3%. This media helps students in understanding abstract concepts to be more concrete and relevant to everyday life. This research makes a significant contribution to mathematics education by providing an innovative model for developing engaging digital learning resources that can improve students' mathematical reasoning skills.Pengembangan Media Pembelajaran Berbasis Animaker Untuk Meningkatkan Kemampuan Penalaran Matematis Siswa Pada Materi PerbandinganABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis Animaker untuk meningkatkan kemampuan penalaran matematis siswa pada materi perbandingan. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Penelitian ini dibatasi hingga tahap Development. Subjek penelitian adalah 23 siswa kelas VIII di SMP Negeri 6 Majalengka. Instrumen yang digunakan dalam penelitian ini adalah observasi, wawancara, dan angket berupa lembar validasi dan lembar praktikalitas. Media pembelajaran yang dikembangkan berupa video animasi yang mengintegrasikan konsep-konsep matematika dengan visualisasi yang menarik untuk memudahkan pemahaman siswa. Hasil penelitian menunjukkan bahwa media pembelajaran berbasis Animaker valid dengan nilai rata-rata validasi ahli media 88,5% dan validasi ahli materi 84%. Kepraktisan media ini juga dinilai sangat baik dengan skor kepraktisan guru sebesar 92,9% dan kepraktisan siswa sebesar 90,3%. Media ini membantu siswa dalam memahami konsep-konsep abstrak menjadi lebih konkrit dan relevan dengan kehidupan sehari-hari. Penelitian ini memberikan kontribusi yang signifikan terhadap pendidikan matematika dengan memberikan model inovatif untuk mengembangkan sumber belajar digital yang menarik dan dapat meningkatkan kemampuan penalaran matematis siswa.Kata Kunci :Animaker; penalaran matematis; perbandingan.